The asymptotic of the density of the k-th maxima of independent random variables - Jokimaitis, Arvydas (Lietuvos matematikos rinkinys, 2023)
In this paper the local limit theorem for density of k-th maxima of independent identically distributed random variables is proved.
Keywords: extreme values; local limit theorems; order statistics